(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
Language serves not only as a tool for communication but also as a reflection of a nation’s culture, history, and perspective. In the field of comparative linguistics, grammatical gaps, referred to as “lacunas” represent one of the most fascinating phenomena that illustrate the distinctive characteristics of different languages. This article offers a comparative examination of grammatical gaps in English and Uzbek, incorporating academic viewpoints, theoretical frameworks, and practical instances